Sustainable options for the utilization of solid residues from wine production. (February 2017) - Zhang, Nansen; Hoadley, Andrew; Patel, Jim; Lim, Seng; Li, Chao'en
Highlights: The valorisation of grape marc of Australian winery was concentrated. Combustion for electricity and pyrolysis for bio-char production were analysed. ASPEN PLUS was used for simulation. Besides carbon-neutral energy, pyrolysis yields high valued bio-char. The selection of profitable utilisation methods depends on the scale of winery. Abstract: The efficient use of solid organic waste materials is an issue of particular importance for the wine industry. This paper focuses on the valorization of grape marc, the major component of winery organic waste (60–70%). Two methods were designed and compared: combustion to generate electricity, and the pyrolysis for the production of bio-char, bio-oil, and bio-gas. Each of these processes was analysed to determine their economic and environmental viability. The flow-sheeting software, ASPEN PLUS, was used to model the two cases. Data from the simulations was used to inform techno-economic and environmental analyses. Pyrolysis was found to be the superior method of utilizing grape marc from both economic and environmental perspectives. Both pyrolysis and combustion exploit the energy content of the waste, which is not recovered by the traditional treatments, composting or distillation. In addition to the production of energy, pyrolysis yielded 151 kg of bio-char and 140 kg of bio-oil per tonne of grape marc. These products may be used in place of fossil fuels, resulting in a net reduction of carbon dioxide emissions. However, the potential deleterious effects resulting from the replacement of the traditional treatments was not considered. Investment in either pyrolysis or combustion had a negligible impact on the price of the wine produced for wineries with an annual grape crush larger than 1000 tonnes. Composting has significant economic advantages in wineries with a small grape crush of less than 50 tonnes.